2004
DOI: 10.1080/00224490409552228
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of gay and lesbian partnering in the larger metropolitan areas of the United States

Abstract: This paper had two objectives. First, we developed for each large metropolitan area of the United States with a population of 500,000 or more in 1990 four indexes of gay partnering and four indexes of lesbian partnering. We compared and related these indexes and their variable measurements with one another. Second, using what we argue is the statistically and demographically preferred set of gay and lesbian partnering rates, we proposed and tested an assortment of ecological hypotheses relating characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…30 We choose to follow an approach used by Walther et al, 31 that calculates a same-sex couple rate per 1000 coupled households, shown for male couples:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 We choose to follow an approach used by Walther et al, 31 that calculates a same-sex couple rate per 1000 coupled households, shown for male couples:…”
Section: Methodsmentioning
confidence: 99%
“…12 Same-sex couples, like other couples, tend to migrate toward regions with better jobs, more temperate weather, lower crime, and cultural amenities. 28,29 Yet, the political environment also matters for samesex couples, with greater concentrations of same-sex couples in less conservative places 30,31 and in regions with higher concentrations of other same-sex couples. 29 Within these regions, however, neighborhood selection can be influenced by several factors: Qualitative research finds strong evidence of the importance of other same-sex couples in neighborhood selection.…”
Section: Original Investigationmentioning
confidence: 99%
“…Census procedures allow respondents to check the ''unmarried partner'' response irrespective of whether the person's sex is the same as that of person #1. Because the ''unmarried partner'' response is meant to reflect a ''marriage-like'' relationship between the two persons, researchers make the reasonable and defensible assumption that data on same-sex households (male-male or female-female) represent households inhabited mainly by partnered gays or by partnered lesbians (Gates and Ost 2004;Walther and Poston 2004;Simmons and O'Connell 2003;Black et al 2000Black et al , 2002Cooke and Rapino 2007;Baumle et al 2009). We discuss next the quality of these data.…”
Section: Datamentioning
confidence: 98%
“…We have already noted that the census questionnaire does not include a question asking specifically about the sexual orientation, or the sexual behavior, or the sexual desire of the respondents. But following the practice of other researchers (Gates and Ost 2004;Walther and Poston 2004;Simmons and O'Connell 2003;Black et al 2000Black et al , 2003Baumle et al 2009), we assume that the census numbers of same-sex male and female partners reflect the numbers of coupled gay men and lesbians in the population. Next, regarding the extent of partnering per se, since there are no national level data available on gay male and lesbian partnering and commitment, and since different studies report different estimates, we employed the male and female averages of the various studies developed by Gates and Ost (2004).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation